Violencia, anticoncepción y embarazo no deseado. Mujeres indígenas en San Cristóbal de Las Casas, Chiapas - Rivas, M. Georgina; Nazar, Aus; Estrada, Erin Jane; Zapata, Emma; Mariaca, Ramón (El Colegio de México A.C., 2009)
This study is part of a qualitative research project conducted in San Cristóbal de Las Casas, Chiapas, Mexico. Interviews with immigrant indigenous women are used to show the influence of social marginalization as well as men’s abuse of power in the origin of unwanted pregnancy. The overvaluation of male knowledge, the expectation of forming a union as a social mandate and as a survival strategy and the violence suffered by women throughout their lie cycle determines their acceptance of sexual relations with scant contraceptive protection.